Implementation of the circular economic model in the Chinese practice - Nemes Zsófia (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The circular economic model is a newly (re)discovered paradigm by the humanity which seems to be inevitable in order to create a sustainable resource managment for our future, in all sectors of the economy, especially in industrial production. Disciplines such as industrial ecology have already shed the light on the importance of copying or adapting nature-based ecosystems in industrial zones, parks, see e.g., the worldwide spreading eco-industrial parks. In many parts of the world, the circular economic is not only emerging as a theoretical concept, but is also being integrated into policy-making processes and practice. The circular economy can also be an alternative to traditional – linear – economic systems on a global scale. The European Union is making a strong move in this direction, as are many other countries, including the United States and China. China is one of the most committed promoters of this concept, where we can talk about the political mainstreaming of the circular economic model since the 1990s. The country is having an exponentially increasing number of pilot projects for circular economic. By implementing the circular economic model, China is reflecting on the complex problems of the very rapid industrialization and economic growth. An extremely centralised political regime like China is using top-down methods which may not be possible to implement neither in the EU nor in the US, but it is rather the system-level thinking of circularity which must be studied, not the concrete plans and steps. This article aims to analyse why circular economy is a beneficial approach to industrial sites, why we may state that the Chinese practice is very unique and specific in a global comparison, and what might be the potential lessons or patterns other countries or regions could study and interprete. The methodology applied by the author is based on the review of recent international literature available on the best practices of circular economic, as well as concrete case studies and statistical data from China. Based on the already existing and published models, it is undebated that the Chinese practice is progressive in quantitative terms, however, there are several weak points of the pilot and demonstration projects, mainly regarding the lowel level of involvement of stakeholders (park managment and business actors) and the density of cooperation networks.

A körkörös gazdasági modell az emberiség által újonnan (újra) felfedezett paradigmája, amely elkerülhetetlennek tűnik jövőnk fenntartható erőforrás-gazdálkodásának megteremtéséhez, a gazdaság minden szektorában, különösen az ipari termelésben. Az olyan tudományágak, mint az ipari környezetvédelem, már rávilágítottak a természet alapú ökoszisztémák másolásának vagy adaptálásának fontosságára az ipari övezetekben, parkokban, lásd például a világszerte terjedő ökoipari parkokat. A világ számos részén a körkörös gazdaság nemcsak elméleti fogalomként jelenik meg, hanem a politikaalkotási folyamatokba és a gyakorlatba is beépül. A körkörös gazdaság globális szinten is alternatívája lehet a hagyományos – lineáris – gazdasági rendszereknek. Az Európai Unió erőteljes lépést tesz ebbe az irányba, akárcsak sok más ország, köztük az Egyesült Államok és Kína. Kína ennek a koncepciónak az egyik legelkötelezettebb hirdetője, ahol a körkörös gazdasági modell 1990-es évektől kezdődő politikai mainstreamingjéről beszélhetünk. Az országban exponenciálisan növekszik a körkörös gazdasági kísérleti projektek száma. Kína a körkörös gazdasági modell megvalósításával a nagyon gyors iparosodás és a gazdasági növekedés összetett problémáira reflektál. Egy olyan szélsőségesen centralizált politikai rezsim, mint Kína, felülről lefelé irányuló módszereket alkalmaz, amelyek megvalósítása az EU-ban és az USA-ban lehetséges lenne, hanem inkább a rendszerszintű körforgás mikéntjét kell tanulmányozni a konkrét tervekkel és lépésekkel ellentétben. Ennek a cikknek az a célja, hogy elemezze, miért előnyös a körkörös gazdaság az ipari telephelyeken, miért állíthatjuk, hogy a kínai gyakorlat globális összehasonlításban nagyon egyedi és specifikus, és mik lehetnek azok a lehetséges tanulságok vagy minták, amelyeket más országok vagy régiók tanulmányozhatnának és implementálhatnak. A szerző által alkalmazott módszertan a körkörös gazdaság legjobb gyakorlataival foglalkozó legújabb nemzetközi szakirodalom áttekintésén, valamint konkrét esettanulmányokon és Kínából származó statisztikai adatokon alapul. A már meglévő és publikált modellek alapján vitathatatlanul megállapítható, hogy a kínai gyakorlat nagyon progresszív, azonban a kísérleti és demonstrációs projekteknek több gyenge pontja is van, elsősorban az érintettek bevonásának alacsony szintje valamint a cooperációs hálózat terhelése miatt.

Резюме. Циркулярна економічна модель (CE) — це новітня парадигма людства, яка здається неминучою для створення сталого управління ресурсами для нашого майбутнього в усіх секторах економіки, особливо в промисловому виробництві. Такі дисципліни, як промислова екологія, вже пролили світло на важливість відтворення або адаптації природних екосистем у промислових зонах та парках, прикладом чого є екопромислові парки, що поширюються у всьому світі. У багатьох частинах світу циркулярна економіка не тільки виникає як теоретична концепція, але також інтегрується в процеси формування політики та практику. Циркулярна економіка також може бути альтернативою традиційним – лінійним – економічним системам у глобальному масштабі. Європейський Союз робить рішучий крок у цьому напрямку, як і багато інших країн, включаючи Сполучені Штати та Китай. Китай є одним із найвідданіших промоутерів цієї концепції, де ми можемо говорити про політичне впровадження циркулярної економічної моделі з 1990-х років. У країні експоненціально зростає кількість пілотних проектів циркулярної економіки. Впроваджуючи модель циркулярної економіки, Китай розмірковує над складними проблемами дуже швидкої індустріалізації та економічного зростання. Надзвичайно централізований політичний режим Китаю, використовує методи «зверху вниз», які, неможливо реалізувати ні в ЄС, ні в США, але потрібно вивчати скоріше системне мислення кругообігу, а не конкретні плани та кроки. Ця стаття має на меті проаналізувати, чому циркулярна економіка є вигідним підходом для промислових об’єктів, чому ми можемо стверджувати, що китайська практика є дуже унікальною та специфічною у глобальному порівнянні, і які можуть бути потенційні уроки чи моделі, які інші країни чи регіони можуть вивчити та імплементувати у власну економіку. Методологія, яка використовувалась під час досліджень, базується на огляді останньої міжнародної літератури та наукових досліджень, щодо найкращої практики циркулярної економіки, а також на конкретних прикладах і статистичних даних Китаю.
A körkörös gazdasági modell megvalósítása a kínai gyakorlatban
Впровадження моделі економіки замкненого циклу в практику Китаю
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: circular economy; eco-industrial parks; China; pilot projects; planning; sustainable industrial production